2011
DOI: 10.1007/s10646-011-0772-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of expression of a 14-3-3 gene in response to copper exposure in the marine alga, Fucus vesiculosus

Abstract: The macro-alga Fucus vesiculosus has a broad global and estuarine distribution and exhibits exceptional resistance to toxic metals, the molecular basis of which is poorly understood. To address this issue a cDNA library was constructed from an environmental isolate of F. vesiculosus growing in an area with chronic copper pollution. Characterisation of this library led to the identification of a cDNA encoding a protein known to be synthesised in response to toxicity, a full length 14-3-3 exhibiting a 71% identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
18
1
1
Order By: Relevance
“…Several genomic studies have provided insight into internal regulative processes in seaweeds, but these investigations were mainly focused on genes involved in carbohydrate synthesis (e.g. Zhou & Ragan, 1995), resistance to toxic metals (Owen et al, 2012) or epiphytes (Weinberger et al, 2011a) and acclimation to abiotic stresses (Dittami et al, 2009;Pearson et al, 2010;Heinrich et al, 2012b) (but see Cosse et al, 2009;de Oliveira et al, 2012). In contrast, cellular processes underlying the induction of anti-herbivory defences have been studied in detail for vascular plants.…”
Section: Introductionmentioning
confidence: 99%
“…Several genomic studies have provided insight into internal regulative processes in seaweeds, but these investigations were mainly focused on genes involved in carbohydrate synthesis (e.g. Zhou & Ragan, 1995), resistance to toxic metals (Owen et al, 2012) or epiphytes (Weinberger et al, 2011a) and acclimation to abiotic stresses (Dittami et al, 2009;Pearson et al, 2010;Heinrich et al, 2012b) (but see Cosse et al, 2009;de Oliveira et al, 2012). In contrast, cellular processes underlying the induction of anti-herbivory defences have been studied in detail for vascular plants.…”
Section: Introductionmentioning
confidence: 99%
“…The MT gene has been identified in bladder wrack (Fucus vesiculosus) by Morris et al [24], which suggested that a protective mechanism against metal exposure exists for this species. Further studies suggest induction in this species following Cu exposure [9], as well as an ability to bind to As, Cd, and Zn [25,26]. This shows potential for MT to be developed as a biomarker in brown seaweeds.…”
Section: Introductionmentioning
confidence: 74%
“…Further studies confirmed its role as a detoxification mechanism for metals, and reported MT binding abilities to Zn, and As [25,26]. However, only Owen, et al [9] confirmed this role in the field in vivo. The study found MT to respond to Cu exposure, and this metal was found to be more important for MT induction, due to a stronger and more significant regression coefficient, compared to Zn and Fe.…”
Section: Metal Toxicity and Mt Inductionmentioning
confidence: 99%
See 2 more Smart Citations